2020
DOI: 10.1186/s12993-020-00171-9
|View full text |Cite
|
Sign up to set email alerts
|

Forced exercise activates the NrF2 pathway in the striatum and ameliorates motor and behavioral manifestations of Parkinson's disease in rotenone-treated rats

Abstract: Background Parkinson's disease (PD) is a common neurodegenerative disorder characterized by progressive loss of nigrostriatal dopaminergic neurons leading to dopamine depletion and problems of movement, emotions, and cognition. While the pathogenesis of PD is not clear, damage of dopaminergic neurons by oxygen-derived free radicals is considered an important contributing mechanism. This study aimed to evaluate the role of treadmill exercise in male Wister rats as a single treatment and as an aid-therapy with L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The mean latency evidenced motor abnormalities associated with PD to fall time, latency to move, several crossed squares, latency to the rear, and several rears performed in rotarod and open field testing, all of which showed poor performance of the rotenone group. In contrast, depressive behavior associated with PD was manifested in the rotenone group as decreased swimming and climbing time and increased immobility time through the forced swim test, confirmed by previous literature reports [ 2 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…The mean latency evidenced motor abnormalities associated with PD to fall time, latency to move, several crossed squares, latency to the rear, and several rears performed in rotarod and open field testing, all of which showed poor performance of the rotenone group. In contrast, depressive behavior associated with PD was manifested in the rotenone group as decreased swimming and climbing time and increased immobility time through the forced swim test, confirmed by previous literature reports [ 2 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the lack of Keap1, Nrf2 is transported toward the hmj.hums.ac.ir http core, sticks to ARE, and expresses Nrf2 genes, including NQO1 and other genes such as glutamate, cysteine ligase, and glutathione (28). Exercise activity along with Q10 supplementation showed that Nrf2, an antioxidant protein mainly produced by ROS, increased during exercise (29). According to our results, exercise stimulates Nrf2 and NQO1 transcription factors, reduces oxidative stress, and enhances antioxidant defense (30).…”
Section: Discussionmentioning
confidence: 99%
“…The apparatus consists of a runway of 50-60 cm. The paws of each rat were painted with non-toxic paint then rats were allowed to walk on the narrow runway on which white paper was placed to take the footprints [41,42]. The test period was videotaped.…”
Section: Footprint Testmentioning
confidence: 99%